Contraceptive Uptake among Post Abortion Clients in Local Population of Sargodha District, Pakistan - Saadia Maqbool, Hina Shan, Lubna Shaheen (Journal of Islamic International Medical College, 2021)
Objective: To determine uptake of contraceptive methods by post abortion clients along with factors influencing the uptake. Study Design: Descriptive cross sectional study.